Polyamine quinoline rhodium complexes: synthesis and pharmacological evaluation as antiparasitic agents against Plasmodium falciparum and Trichomonas vaginalis1. Issue 33 (7th September 2015) - Stringer, Tameryn; Taylor, Dale; Guzgay, Hajira; Shokar, Ajit; Au, Aaron; Smith, Peter J.; Hendricks, Denver T.; Land, Kirkwood M.; Egan, Timothy J.; Smith, Gregory S.
<x xml:space="preserve">Abstract</x> Salicylaldimine ligands and their corresponding Rh(i) complexes were prepared and evaluated as antiparasitic agents.